Effect of Partial Replacement of Yam Peel Meal Dioscorea Spp. for Maize Meal Zea mays on Performance and Carcass Characteristics of Finisher Broiler Chicks - Ekenyem, B.U.; Madubuike, F.N.; Dike, O.F. (International Journal of Poultry Science, 2006)
One hundred and sixty 4-week old Anak 2000 broiler chicks were used in a 28-day feeding trial to evaluate the effect of partial replacement of yam peel meal (YPM) for Maize Meal (MM) in the performance and carcass characteristics of finisher broiler chicks. Birds were grouped into four treatments and fed diets containing 0%, 5%, 10% and 15% YPM. The treatments were replicated four times in a completely randomized design. Feeding and potable water supply were ad libitum. Routine vaccination and medication and other standard management practices were strictly observed. Data collected were performance parameters such as initial weight, final weight, weight gain, feed intake, feed conversion ratio and feed cost per kg gain while carcass parameters such as dressed weight, breast weight, thigh weight, wings, shank and head were measured. Results show that birds fed 15% YPM 1737.50g were significantly (P< 0.05) heavier than others fed 0% YPM 1650.00g, 5% YPM 1637.50g and 10% YPM 1675.00g thus showing heavier weight with increasing levels of YPM in the diets. Similar trend was also observed in weight gain in which birds fed 15% YPM made significantly (P< 0.05) superior gain to birds on the rest diets. Cost of feed/kg gain significantly (P< 0.05) reduced with increasing levels of YPM. All carcass parameters show significant (P< 0.05) differences between treatments in favour of birds fed higher levels of YPM. Thus the inclusion of YPM in diets up to 15% improved the performance and carcass characteristics of the birds as well as significantly (P< 0.05) reduced the cost of feed/weight gain.